Amurensin H, a Derivative From Resveratrol, Ameliorates Lipopolysaccharide/Cigarette Smoke-Induced Airway Inflammation by Blocking the Syk/NF-κB Pathway - Yannan Fan; Ziqian Zhang; Chunsuo Yao; Jinye Bai; Hui Yang; Pei Ma; Yiyao Fan; Shuyi Li; Jiqiao Yuan; Mingbao Lin; Qi Hou (Frontiers Media S.A., 2019)
Amurensin H, a resveratrol dimer derived from Vitis amurensis Rupr, has several biological effects, including anti-inflammatory and antioxidant activities. Studies have found that amurensin H attenuated asthma-like allergic airway inflammation. However, its protective activity on chronic obstructive pulmonary disease (COPD) airway inflammation is not fully explored. The present study used a lipopolysaccharide (LPS)/cigarette smoke-induced mice model and an LPS-stimulated THP-1-derived macrophages model to measure the lung tissue's morphology changes. The results showed that amurensin H ameliorated the histological inflammatory alterations in the lung tissues, leading to a decrease in the expression of interleukin 6 (IL-6), IL-17A, tumor necrosis factor α (TNF-α), and interferon γ in bronchoalveolar lavage fluid. Amurensin H also significantly inhibited the release of IL-1β, IL-6, IL-8, and TNF-α in LPS-stimulated THP-1-derived macrophages. Furthermore, amurensin H markedly inhibited the expressions of p-Syk, nuclear factor κB (NF-κB), and p-NF-κB both in vivo and in vitro. Results from cotreatment with Syk inhibitor BAY61-3606 and NF-κB inhibitor BAY11-7082 in vitro revealed that amurensin H's protective effect against airway inflammation could be due partly to the inhibition of the Syk/NF-κB pathway. These findings suggest that amurensin H shows therapeutic effects on COPD airway inflammation, and inhibiting the Syk/NF-κB pathway might be part of its underlying mechanisms.